Energy dependent reinforcement learning based on the neuronal mechanisms of the olfactory processing in mushroom body - Jiang, Jiamu (2024)
The metabolic energy is crucial for neural processing related to learning, which modulates computational capabilities, neuronal quantities, synaptic connections, and long-term memory formation. From the evolutionary perspective, these neural processes have shaped organisms' adaptive responses to environmental stimuli and enhanced survival chances. Studies have highlighted that associative conditioning extends the lifespan across various species. Also, insects modulate memory types based on ecological determinants.